2021
DOI: 10.3389/fimmu.2021.595369
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Activated Bone Marrow-Derived Dendritic Cells Suppress Allergic Airway Inflammation by Ameliorating the Immune Microenvironment

Abstract: BackgroundPrevious studies have shown that lipopolysaccharide (LPS)-activated bone marrow-derived dendritic cells (DClps) might induce tolerance in autoimmune and cancer models in vivo, whereas it remains unclear whether DClps could play a role in allergic disease model. Herein, we aimed to elucidate the potential effects of DClps on OVA-sensitized/challenged airway inflammation in a mouse model, which may help facilitate the application of specific tolerogenic dendritic cells (tolDC) in allergic asthma in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…Hence, we reasoned that the low number of eosinophils and low IL-5 production might be related to the inhibitory effect of the predominant Th1 immunity developed in IL-10-deficient mice. Since in vitro-generated BM-DCs have been employed to modulate allergic airway Th2 responses [37][38][39][40] as well as Th1 activities [41][42][43], we generated BM-DCs from IL-10 −/− or WT mice to address more directly the role of IL-10 on DCs. We found that sensitizations with BM-DCs from WT or IL-10 −/− mice primed with OVA could induce allergic lung inflammation after OVA challenge and that the addition of CpG-ODN prevented the development of allergic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we reasoned that the low number of eosinophils and low IL-5 production might be related to the inhibitory effect of the predominant Th1 immunity developed in IL-10-deficient mice. Since in vitro-generated BM-DCs have been employed to modulate allergic airway Th2 responses [37][38][39][40] as well as Th1 activities [41][42][43], we generated BM-DCs from IL-10 −/− or WT mice to address more directly the role of IL-10 on DCs. We found that sensitizations with BM-DCs from WT or IL-10 −/− mice primed with OVA could induce allergic lung inflammation after OVA challenge and that the addition of CpG-ODN prevented the development of allergic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Under varying circumstances, LPS not only induces the maturation of DCs to exert immune responses but also enables DCs to initiate immunosuppressive functions (20,27). It is widely accepted that DCs acquire endotoxin tolerance after repeated exposure to sublethal LPS in vivo (20,28,29), whereas this phenomenon remains uncertain in vitro. Considering the persistent inflammation during sepsis and the potential regulatory effects of LPS, it is imperative to establish a model for inducing tolDCs through prolonged stimulation with LPS to investigate their role in chronic inflammatory pathology.…”
Section: Introductionmentioning
confidence: 99%
“…These protocols use various immunosuppressive agents, including rapamycin, dexamethasone, and vitamin D, as well as inhibitory cytokines such as IL-10 and TGF-β, to alleviate excessive and undesired immune responses (16,18,19). Furthermore, IL-10 has been identified as the most potent pharmacological agent for inducing tolDCs among these options (20,21). However, a major limitation of tolDCs is their inability to accurately represent the pathophysiology of sepsis in terms of chronic low-grade inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most dendritic cells in vivo are in an immature and inactive state. Consequently, they can be converted to a mature and active state with different phenotypic and functional characteristics by exposure of these cells to different stimulatory ligands [10].…”
Section: Introductionmentioning
confidence: 99%